Association of Cesarean Birth with Body Mass Index Trajectories in Adolescence - Zhou, Yunping (Int J Environ Res Public Health, 2020)
Background: This study aimed to identify patterns of body mass index (BMI) changes in adolescence and to assess whether delivery mode (Cesarean and vaginal delivery) was associated with BMI trajectories. Methods: This study was conducted among 569 adolescents aged 10–15 years that resided in the city of Zibo, China. The height and weight of each participant were repeatedly measured at 10, 11, 12, 13, 14 and 15 years. Group based trajectory modeling (GBTM) was used to estimate BMI change trajectories, and multinomial logistic regression was conducted to evaluate the independent association of delivery mode and BMI trajectory classes. Results: Of the 569 participants, 407 (71.5%) were vaginal deliveries and 162 (28.5%) were Cesarean deliveries. Five distinct long-term BMI trajectories were identified: “persistent healthy weight” (57.5%), “persistent underweight” (6.5%), “obesity to healthy weight” (7.8%), “progressive overweight” (10.6%), “progressive obesity” (17.6%). Adjusted multinomial logistic models revealed a twofold increase in risks between ages 10–15 years of “progressive obesity” trajectory (OR = 2.50, 95% CI: 1.42, 4.41) for children born through Cesarean section compared with vaginal birth. Conclusions: Five distinct long-term BMI trajectories were identified during adolescence in our research, and we confirmed that Cesarean birth was significantly increased the risk of “progressive obesity” trajectory but not the “obesity to healthy weight” trajectory.